2008
DOI: 10.1093/qjmed/hcm125
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal tuberculosis in a district general hospital: a retrospective review of 86 cases

Abstract: The diagnosis can be difficult to make because of the varied presentation, the low percentage with positive microscopy for acid-fast bacilli and the time delay of up to several weeks for a positive TB culture. The thresholds for laparoscopy and/or laparotomy for the diagnosis were therefore very low. The diagnosis could be made rapidly by these methods, and early treatment instituted. Six months short-course chemotherapy is very effective in ATB. This should be changed, if appropriate, on the basis of drug sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 26 publications
7
49
0
5
Order By: Relevance
“…The male female ratio is highly variable from equal in the series reported by Ramesh et al 80 to a male predominance reported in two studies 56,79 and to a marked female predominance in the study of Nafeh et al 78 In our series the male: female ratio of 1:3. The reasons for these variations are unclear.…”
Section: Clinical Characteristicssupporting
confidence: 40%
See 3 more Smart Citations
“…The male female ratio is highly variable from equal in the series reported by Ramesh et al 80 to a male predominance reported in two studies 56,79 and to a marked female predominance in the study of Nafeh et al 78 In our series the male: female ratio of 1:3. The reasons for these variations are unclear.…”
Section: Clinical Characteristicssupporting
confidence: 40%
“…78,80 U/S abdomen was suggestive of tuberculosis in all patients, but histology/culture results were positive in 55 patients. Though the sensitivity of CT scan was high, the specificity was very low in our series.…”
Section: Imagingmentioning
confidence: 92%
See 2 more Smart Citations
“…Ileocecal tuberculosis was managed by right hemicolectomy with or without stoma, perforation along with multiple stricture resection anastomosis with a covering stoma or only stoma [22,23]. Typhoid enteric perforations were managed by either primary repair or only stoma, depending on the condition of the gut and general condition of the patient and also managed laparoscopically [24].…”
Section: Discussionmentioning
confidence: 99%